Epidemiological analysis reveals coral species affected by stony coral tissue loss disease present a similar epizootic progression despite differences in susceptibility and population impact - Edgar Omar Guzmán-Urieta; Eric Jordán-Dahlgren; Lorenzo Alvarez-Filip (PLoS ONE, 2026)
Stony coral tissue loss disease (SCTLD) is one of the most aggressive coral syndromes recorded, affecting over 30 scleractinian species and causing high mortality rates. Despite its impact, most available information is derived from assessments that estimate prevalence at a single point in time, rather than examining its temporal dynamics. This study analyzed the susceptibility of 16 coral species to SCTLD and tracked the 2018–2019 outbreak on a fringing reef in the Mexican Caribbean using epidemiological methods commonly employed in human epidemics but rarely in coral epizootics. Between June 2018 and July 2019, we monitored 990 coral colonies. For each affected colony, we estimated the progression of tissue death over time, allowing us to identify the days of lesion onset and total tissue mortality. To assess vulnerability and provide a detailed prognosis of outbreak progression, magnitude, and severity during the epizootic we employed epidemic curves, Kaplan-Meier risk and survival functions, and measures of period prevalence and mortality. Epidemiological parameters from these analyses were integrated into a multi-dimensional framework for a comprehensive assessment of coral susceptibility. Our findings revealed that species-specific susceptibility was associated with the risk, magnitude, and severity of the epizootic but not with its progression. Temporal analyses revealed community-level patterns, including secondary outbreak waves following increases in mortality. This suggests a potential feedback mechanism, where mortality may contribute to secondary transmission events, a phenomenon not previously described in the study of coral epizootics. As a contribution to the characterization of coral susceptibility to SCTLD, we outline a four-level framework based on diverse epidemiological indicators, beyond prevalence. This approach revealed a higher-than-expected susceptibility in Siderastrea siderea, Agaricia agaricites and Agaricia tenuifolia, compared to previous studies. This study underscores the importance of epidemiological approaches in investigating coral epizootics. By challenging traditional reliance on prevalence measurements, our findings offer a novel perspective on coral disease dynamics.